PENERAPAN TEKNIK COGNITIVE BEHAVIOR THERAPY DALAM LAYANAN KONSELING KELOMPOK UNTUK MENGURANGI TRAUMA BODY SHAMING PADA SISWA KELAS X SMA N 1 BAE KUDUS - Nanda Gita Pratiwi; Indah Lestari; Richma Hidayati (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
Body shaming is an act of commenting on a person's physical circumstances in a way that makes fun of the surrounding body. The objective of this study is to: 1) Discredit the implementation of group counselling. Cognitive behavior therapy techniques to reduce body shaming. 2) Discover how to reduce the body shaking through the technique of cognitive conduct therapy in students. By providing understanding to students about reducing the body Shaming, then the researchers are able to implement the group counseling services. The study of action of this class is carried out in stages: 1. Planning, 2. Implementation, 3. Observation, 4. Reflection is performed in 2 cycles of research, each cycle is conducted three times meetings. The subjects of this study are eight students/students X E-3 of SMA N 1 Bae. Data collection techniques include interviews, observations, and documentation techniques. The results of the study were the condition in pre-cycle students who suffered body shaming obtained a presentation score of 86% with category “Very high”, at the first meeting of cycle I students obtain a presentation score of 82% with the category “very high”, meeting of the second cycle students receive a presentation point of 80% with the categories “high”, at meeting of third cycle 1 students obtaining a score of 72% with category "High". Cycle II first meeting students get a presentation of 49% with a category “low”, meeting second student obtains a presentation scoring of 40% with the kategories “very low”, meeting third of the cycle II students get 36% in the category "very low". The conclusion is that group counselling services Technical cognitive behavior therapy can reduce bodily shaming in students of X E-3 SMA N 1 Bae.